2021
DOI: 10.3390/biomedicines9010057
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Pulmonary Hypertension: Cause or Consequence?

Abstract: Pulmonary arterial hypertension (PAH) is a rare, complex, and progressive disease that is characterized by the abnormal remodeling of the pulmonary arteries that leads to right ventricular failure and death. Although our understanding of the causes for abnormal vascular remodeling in PAH is limited, accumulating evidence indicates that endothelial cell (EC) dysfunction is one of the first triggers initiating this process. EC dysfunction leads to the activation of several cellular signalling pathways in the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 192 publications
(133 reference statements)
2
61
0
1
Order By: Relevance
“…It is now recognized that perivascular inflammation is a common contributing factor in almost all forms of PH [ 103 , 104 , 105 , 106 ] because inflammatory cell infiltrates comprising T- and B-lymphocytes and macrophages have been identified. Upon endothelial cell injury, HPAECs become dysfunctional and alter their secretion of cytokines and other factors that regulate coagulation, thrombosis, and vascular tone [ 107 ]. However, the exact mechanisms by which inflammation might facilitate the progression of PH are still under investigation.…”
Section: Jak/stat Pathway and Cellular And Molecular Dysregulation In Pulmonary Hypertensionmentioning
confidence: 99%
“…It is now recognized that perivascular inflammation is a common contributing factor in almost all forms of PH [ 103 , 104 , 105 , 106 ] because inflammatory cell infiltrates comprising T- and B-lymphocytes and macrophages have been identified. Upon endothelial cell injury, HPAECs become dysfunctional and alter their secretion of cytokines and other factors that regulate coagulation, thrombosis, and vascular tone [ 107 ]. However, the exact mechanisms by which inflammation might facilitate the progression of PH are still under investigation.…”
Section: Jak/stat Pathway and Cellular And Molecular Dysregulation In Pulmonary Hypertensionmentioning
confidence: 99%
“…Amabile et al reported an increased number of circulating EMVs in a mixed group of patients with different pulmonary hypertension aetiologies, including PAH and chronic pulmonary disease–related pulmonary hypertension, which correlated to disease severity [ 14 , 25 ]. Additionally, in PAH, EMVs have been considered key modulators in inflammatory and coagulation PAH-associated processes [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAH is a life-threatening disorder consisting in a progressive increase in pulmonary vascular resistance, which can ultimately lead to right heart failure and patient’s death. PAH is triggered by endothelial injury, which paves the way to the emergence of apoptosis-resistant and hyperproliferative endothelial cells that display impaired release of vasorelaxing mediators and contribute to the formation of occlusive intimal lesions [ 306 , 307 ]. In addition, pulmonary-resident ECFCs could support the proliferative angiopathic process in PAH [ 308 ].…”
Section: Therapeutic Applications and Pathological Implications Of Ros-induced Endothelial Ca 2+ Signalsmentioning
confidence: 99%